DOES ASEAN5+3 NEED COMMON CURRENCY? (ANALYSIS OF OPTIMUM CURRENCY AREA INDEX 2008-2016) - Elisabeth, Christina Ruth (Journal Economics & Business Atmajaya Indonesia, 2018)
The purpose of this study is to analyze the benefit-cost of currency union in ASEAN5 + 3 countries. The analysis was conducted by calculating OCA index by using Bayoumi and Eichengreen model.  The estimation of the bilateral index shows that the lowest OCA index for ASEAN5+3 relationship exist in the relationship of Singapore-China, China-Philippines and China-Thailand. Currency unification can be start from Singapore-Thailand-Philippines, followed by Chinese Renminbi currency. Then, it can continue to integrate Korean and Malaysian currency. Meanwhile, Indonesia and Japan are least suitable for adopting common currency due to the high cost that reflected in the high OCA index. The result of Fixed Effect panel regression shows that trade intensity, size of economy and export dissimilarity significantly influence exchange rate volatility in ASEAN5+3 countries. Meanwhile, in terms of dissimilarity of export commodities, the result shows different relationship direction from expectation. Thus, this study recommends the need for further research involving variables of intra-industry trade and global value chain.